Edukasi Potensi Tanaman Obat dalam Pengobatan Luka Bakar di Desa Medan Sinembah - Rahmadani Rahmadani; Supiyani Supiyani; Ainil Fithri Pulungan; Yayuk Putri Rahayu (Jurnal SOLMA, 2026)
Background: Burns are a common injury in the household and can lead to infectious complications if not treated properly. Using medicinal plants as an alternative, complementary therapy based on local wisdom can increase community knowledge and independence in treating minor burns, while also enhancing their knowledge and independence in maintaining health. Therefore, this community service activity aims to increase the Medan Sinembah Village community's knowledge of the potential of medicinal plants and how to use them properly and safely as first aid for minor burns. Methods: The community service activity was implemented in four stages: education, demonstration, and evaluation. The education phase involved delivering materials and leading interactive discussions on the types, potential, benefits, and methods of using medicinal plants for first aid for minor burns. Subsequently, the team demonstrated simple, appropriate processing and application of medicinal plants. Evaluation measured participants' knowledge after the activity and assessed their satisfaction with the education. Results: The evaluation showed increased participant knowledge, with the average pre-test score of 60% increasing to [value] on the post-test, representing a 95% increase in knowledge. Participants also gained an understanding of the potential and use of medicinal plants, particularly aloe vera and binahong leaves (Anredera cordifolia), as complementary first-aid therapies for minor burns. Conclusion: Education on the potential of medicinal plants effectively increased community knowledge and skills in using medicinal plants for first aid for minor burns. This program supports community empowerment based on local wisdom and promotive-preventive health practices.